2022
DOI: 10.5219/1732
|View full text |Cite
|
Sign up to set email alerts
|

Acclimatization of fish to the higher calcium levels in the water environment

Abstract: It is established that calcium concentration changes (variations) in the water environment significantly influence its intake and distribution in tissues and organs of hydrobionts. The decrease in calcium concentration in water from 100 to 60 mg.L-1 significantly reduces its content in fish liver. In the gills glandular apparatus of fish acclimated to the environment with lower calcium level (in comparison with control one), its concentration on the first day of the acclimation period slightly exceeded the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
1
0
1
Order By: Relevance
“…However, it should be noted that the opinion of researchers regarding the dependence between the absorption of phosphorus from the aquatic habitat and its level in it is somewhat contradictory. Thus, (Dilelis et al, 2021;Hrynevych et al, 2022) had been shown that with phosphorus concentration increases in the aquatic environment, its accumulation by fish also increases. At the same time, a high number of phosphorus can adversely influence the branchial membranes, thereby reducing the actual absorption and phosphorus transport (Villeger et al, 2017).…”
Section: Note: * Reliable Results Source: Compiled By the Authorsmentioning
confidence: 99%
“…However, it should be noted that the opinion of researchers regarding the dependence between the absorption of phosphorus from the aquatic habitat and its level in it is somewhat contradictory. Thus, (Dilelis et al, 2021;Hrynevych et al, 2022) had been shown that with phosphorus concentration increases in the aquatic environment, its accumulation by fish also increases. At the same time, a high number of phosphorus can adversely influence the branchial membranes, thereby reducing the actual absorption and phosphorus transport (Villeger et al, 2017).…”
Section: Note: * Reliable Results Source: Compiled By the Authorsmentioning
confidence: 99%
“…Використання дистанційного навчання впродовж останніх років вказує на достатньо високу, якісну успішність здобувачів вищої освіти та підготовку науково-педагогічного персоналу для забезпечення освітньої програми Водні біоресурси та аквакультура у Білоцерківському національному аграрному університеті. Студенти забезпечені електронними варіантами посібників, підручників, курсів лекцій, презентацій, наукових публікацій за тематикою курсу на платформі Moodle (Kofonov et al, 2020;Vodianitskyi et al, 2020;Prychepa et al, 2021;Hrynevych et al, 2021;2022;Liasota et al, 2023).…”
Section: висновкиunclassified